Degradation of wheat straw/polylactic acid composites by Aspergillus niger. Issue 3 (2nd February 2022) - Chai, Xicun; He, Chunxia; Liu, Yutao; Niyitanga, Evode; Zhou, Yu; Wang, Luyang; Zhang, Weixing
Abstract: Polylactic acid has good biodegradability and it is dosage is increasing. Therefore, the degradation of PLA has become a new problem that needs serious management. In this study, the spores of Aspergillus niger were inoculated onto wheat straw/PLA composites containing different contents of sodium alginate, and the mass loss and characterization (microstructure, fourier transform infrared spectroscopy, thermal properties, and X‐ray diffraction) of the composites were detected. The objective was to explore the possibility of degradation of PLA composites by A. niger and the effect of sodium alginate on the degradability of PLA composites. The results showed that when the amount of sodium alginate was 3% and 6%, the mass loss rate of the composites only increased at the initial stage of degradation. However, when the amount of sodium alginate was 9%, the mass loss rate of the composites was significantly increased. It was found that A. niger could colonize the surface of the composites and cause cracks and depressions on the surface by morphological observation. The infrared spectral curve showed that the number of hydroxyl and carbonyl groups in the composites increased after degradation. According to the thermogravimetric curve of the composites, the pyrolysis temperature of the composites with sodium alginate content of 9% increased and the residual mass decreased after degradation. When the amount of sodium alginate was 9%, the crystallinity of the composites was greatly reduced, and it is crystallization zone was easier to degrade compared with other treatments. The results would provide a theoretical support for the rapid degradation of PLA composites. Abstract : The possibility of PLA composites degraded by Aspergillus niger were clarified through degradation tests. A. niger could colonize the surface of PLA composites. Sodium alginate (9%) could greatly reduce the crystallinity of PLA composites, and then improve the degradability of composites.